Nasal carriage of CTX-M-55-producing Escherichia coli ST8369 in a healthy cohort in the city of Yangzhou, China - Wang, Zhen-Yu; Jiang, Yue; Shao, Yi-Qiao; Lu, Heng-Fan; Lu, Meng-Jun; Jiao, Xinan; Li, Qiu-Chun; Wang, Jing (Frontiers in Cellular and Infection Microbiology, 2022)
This study aimed to investigate the prevalence and diversity of extended-spectrum β-lactamases (ESBL)-producing Escherichia coli isolates from healthy individuals in a community and to elucidate their dissemination mechanism. Cefotaxime-resistant E. coli were isolated from 95 samples of healthy persons from one community in Yangzhou, China, and were tested for minimal inhibitory concentrations of 14 antimicrobial agents. The isolates were subjected to whole genome sequencing by Illumina Hiseq or PacBio single-molecule real-time sequencing. A total of 30 cefotaxime-resistant E. coli isolates were obtained, carrying blaCTX-M (n=29) or blaDHA (n=1), of which the blaCTX-M-55 (n=19) was the most predominant genotype. One novel blaCTX-M variant blaCTX-M-252 was identified. Thirteen CTX-M-55-producing E. coli isolates belonged to ST8369 from nasal (n=12) or faecal (n=1) samples shared the identical cgMLST type, resistance profiles, resistance genes, plasmid replicons, and a 5,053-bp blaCTX-M-55 structure ΔIS26-ΔISEcp1-blaCTX-M-55-Δorf477-ΔTn2. The blaCTX-M-55 gene was located on IncHI2/ST3 plasmid in E. coli ST8369. The lengths of blaCTX-M/blaDHA-carrying contigs in the remaining 17 E. coli strains ranged from 1,663 to 382,836 bp, located on chromosome (n=4) or plasmids (n=5); the location of the other eight contigs could not be determined due to incomplete assembly. The blaCTX-M was associated with ISEcp1 as previously reported. Nasal colonization of CTX-M-55-producing ST8369 E. coli strains has occurred among healthy individuals in one community. There is a potential risk of antimicrobial resistance dissemination between humans within one community through close contact or environment via aerosols or dust. Therefore, surveillance of nasal carriage of blaCTX-M in communities is warranted to further monitor the spread of the antimicrobial resistance genes in China.